Taxonomy of ’Euconnus complex’. Part VII. Glabriconnus, a new subgenus of Euconnus from Madagascar (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2016)
A new subgenus of Euconnus Thomson is described, Glabriconnus subgen. n., to accommodate four Madagascan species: Euconnus banari sp. n. (type species of Glabriconnus), E. andranomenaus sp. n., E. februarius sp. n. and E. aterrimus Franz (transferred from Euconnus s. str.). Morphological structures of the new taxa are illustrated and described in detail, and possible relationships of Glabriconnus are discussed. The new subgenus is most similar to Tetramelus Motschulsky and Paratetramelus Franz in gradually thickened antennae and reduction of wings and associated structures, but the four species included in Glabriconnus share a unique synapomorphy, a hypomeral groove at each side of pronotum. They also have a broad, short and flattened ’anthiciform’ head; nearly glabrous head, pronotum and elytra, except for thick bristles on genae, postgenae (but not tempora) and along anterior and lateral pronotal margins, and pronotum with one pair of distinct lateral pits.